Colletion variations and drying temperature in the essential oil inflorescences of Hyptis marrubioides (Research, Society and Development, 2021)
Hyptis marrubioides Epling is popularly known as field mint and is part of the Lamiaceae family. It is a characteristic species of the Brazilian Cerrado, whose medicinal properties of essential oil have already been scientifically proven. Through the various factors that influence the content and chemical composition of the essential oil, the objective was to identify which conditions of collection and drying temperature of the inflorescences provide higher essential oil content and possible chemical variations of the volatile fraction. An experiment was carried out in a completely randomized design (DIC), in a factorial scheme. Two collection positions of H. marrubioides inflorescences on the parent plant (apical and median) and two drying temperatures of the plant material (40 and 60ºC) were studied, totaling four treatments, with analyzes in duplicates. The essential oil was extracted by steam drag and subsequently chemical analysis of four experimental plots was carried out using Gas Chromatography Coupled to Mass Spectrometry (GCEM). It is concluded that the apical position of the inflorescences of Hyptis marrubioides has a higher essential oil content, especially when subjected to a drying temperature of 60ºC. Variations in the collection position and drying temperature provided quantitative and qualitative changes in the chemical analysis of the essential oil from H. marrubioides inflorescences.